The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00401-022-02469-6
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 is elevated in CSF and is associated with Aβ deposits and tau aggregates in brain tissue in Alzheimer’s disease

Abstract: Galectin-3 (Gal-3) is a beta-galactosidase binding protein involved in microglial activation in the central nervous system (CNS). We previously demonstrated the crucial deleterious role of Gal-3 in microglial activation in Alzheimer’s disease (AD). Under AD conditions, Gal-3 is primarily expressed by microglial cells clustered around Aβ plaques in both human and mouse brain, and knocking out Gal-3 reduces AD pathology in AD-model mice. To further unravel the importance of Gal-3-associated inflammation in AD, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
2
14
3
Order By: Relevance
“…Indeed, neuroinflammatory response has been linked to synaptic dysfunction 64 . We also demonstrated a positive relationship between CSF Gal‐3 levels and t‐tau in AD patients along with GAP‐43 and neurogranin, markers of synaptic dysfunction 24 . However, in this study no association was found between Gal‐3 and p‐tau 181, contrary to our previous study in AD patients where we observed a significant association 24 .…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Indeed, neuroinflammatory response has been linked to synaptic dysfunction 64 . We also demonstrated a positive relationship between CSF Gal‐3 levels and t‐tau in AD patients along with GAP‐43 and neurogranin, markers of synaptic dysfunction 24 . However, in this study no association was found between Gal‐3 and p‐tau 181, contrary to our previous study in AD patients where we observed a significant association 24 .…”
Section: Discussioncontrasting
confidence: 90%
“…Our study also confirmed that Gal‐3 acts as an endogenous TREM2 ligand, a central player in the regulation of microglial activation under disease conditions 21 . It is important to note that in AD we found Gal‐3 in cerebrospinal fluid (CSF) to be strongly associated with neuroinflammation markers, synapse loss, and cognitive decline 24 . A recent study analyzing over 2000 human AD brain tissue samples identified a microglia module as a highly affected process in AD.…”
Section: Introductionsupporting
confidence: 79%
“… 13 15 , 29 31 Recently, Gal-3 was identified as a cerebrospinal fluid biomarker in Alzheimer's disease which correlated with markers of neuronal degeneration, synaptic dysfunction, and neuroinflammation. 43 Gal-3 and Apoe are also upregulated in microglia in mouse models of glaucoma 19 and photoreceptor degeneration, 20 as well as in human postmortem glaucomatous tissues. 19 We therefore hypothesize that these molecules may be released from activated retinal microglia into the vitreous chamber, thereby reaching the anterior chamber of the eye.…”
Section: Discussionmentioning
confidence: 97%
“…There are many studies leveraging the Gal-3’s pivotal role in AD pathophysiology [ 153 , 154 ]. Recent observational studies unraveled a substantial increase in the Gal-3’s serum and CSF level in AD cases compared to the control group [ 155 157 ]. An experiment conducted by Tao et al exhibited a concordant rise in Gal-3 and Aβ oligomerization in the frontal lobe of AD patients [ 158 ].…”
Section: Microglia Impairment Heralds Brain Connectivity Dysfunctionmentioning
confidence: 99%